Once upon a frog - Mlynowski, Sarah (Mlynowski, Sarah. Whatever after, 2016)
Abby is worried because Jonah has the fairy Maryrose's memories mixed up with his own, but when they try to talk to her they get sucked through the mirror and find themselves in the story of The Frog Prince.